Structures of rhenium(I) complexes with 3‐hydroxyflavone and benzhydroxamic acid as O, O′‐bidentate ligands and confirmation of π‐stacking by solid‐state NMR spectroscopy. Issue 4 (5th March 2019) - Schutte-Smith, Marietjie; Roodt, Andreas; Alberto, Roger; Twigge, Linette; Visser, Hendrik Gideon; Kirsten, Leo; Koen, Renier
Abstract : The synthesis and crystal structures of two new rhenium(I) complexes, obtained utilizing benzhydroxamic acid and 3‐hydroxyflavone as bidentate ligands, are reported. Furthermore, the crystal structure of free 3‐hydroxyflavone was redetermined at 100 K in order to compare the packing trends and solid‐state NMR spectroscopy with those of the solvate flavone molecule. Abstract : The synthesis and crystal structures of two new rhenium(I) complexes obtained utilizing benzhydroxamic acid (BHAH) and 3‐hydroxyflavone (2‐phenylchromen‐4‐one, FlavH) as bidentate ligands, namely tetraethylammonium fac ‐(benzhydroxamato‐κ 2 O, O ′)bromidotricarbonylrhenate(I), (C8 H20 N)[ReBr(C7 H6 NO2 )(CO)3 ], 1, and fac ‐aquatricarbonyl(4‐oxo‐2‐phenylchromen‐3‐olato‐κ 2 O, O ′)rhenium(I)–3‐hydroxyflavone (1/1), [Re(C15 H9 O3 )(CO)3 (H2 O)]·C15 H10 O3, 3, are reported. Furthermore, the crystal structure of free 3‐hydroxyflavone, C15 H10 O3, 4, was redetermined at 100 K in order to compare the packing trends and solid‐state NMR spectroscopy with that of the solvate flavone molecule in3 . The compounds were characterized in solution by 1 H and 13 C NMR spectroscopy, and in the solid state by 13 C NMR spectroscopy using the cross‐polarization magic angle spinning (CP/MAS) technique. Compounds1 and3 both crystallize in the triclinic space group P with one molecule in the asymmetric unit, while4 crystallizes in the orthorhombic space group P 21 21 21 . Molecules of1 and3 generate one‐dimensional chains formed through intermolecular interactions. A comparison of the coordinated 3‐hydroxyflavone ligand with the uncoordinated solvate molecule and free molecule4 shows that the last two are virtually completely planar due to hydrogen‐bonding interactions, as opposed to the former, which is able to rotate more freely. The differences between the solid‐ and solution‐state 13 C NMR spectra of3 and4 are ascribed to inter‐ and intramolecular interactions. The study also investigated the potential labelling of both bidentate ligands with the corresponding fac ‐ 99m Tc‐tricarbonyl synthon. All attempts were unsuccessful and reasons for this are provided.